Low Cost Moringa Seeds and Terminalia Kernels Water Purifier: A Water Management Technology - Mortera, Annabelle F. (JPAIR Multidisciplinary Research, 2017)
The study aimed to develop a low cost water purifier in treating ground water utilizing indigenous plant materials such as the seeds of the Moringa oleifera Lam as the main flocculant and the kernels of the Terminalia catappa Linn. which is the activated carbon adhering to the principles and practices of green technology. Ground water samples from three local communities in Zamboanga City, namely, Talisayan in the west cost, Bungiao in the east cost and San Roque in the city proper were gathered conforming to the standard procedures of the Department of Science and Technology (DOST). Some water parameters were tested using the gadget and these were compared with the standard values set by the Philippine National Standard for Drinking Water (PNSDW). A survey questionnaire of four point Likert scale was employed in determining the acceptability of the gadget among sixty four respondents from the three communities. The weighted mean was use in treating the data. The findings revealed that the gadget which is made of a four layer stainless steel containing the de fatted moringa press cake (MPC), the terminalia granulated activated carbon (TGAC), the sand and the pebbles has the capacity to improve the quality of ground water based from the result of the laboratory tests conducted by the Depratment of Science and Rechnology in Zamboanga City as against the standard values of the Philippine National Standard for Drinking Water on the following parameters, pH total dissolved solids (TDS), hardness and total coliform count (TCC0 and odor.
Keywords: Water Management Technology; water purifier; Moringa oleifera Lam; experimental design; Philippines